Hydrogen bond mediated open-frame networks in coordination polymers: supramolecular assemblies of Pr(III) and 3,5-dinitro-4-methylbenzoic acid with aza-donor compounds - Varughese, S; Pedireddi, VR (Chemical Communications, 2005)
A coordination assembly of 3,5-dinitro-4-methylbenzoic acid and Pr(III), synthesized by hydrothermal methods forms a host structure, which is stable up to 300 degrees C, through C-H center dot center dot center dot O hydrogen bonds and accommodates different types of guest species varying from simple molecules like water to larger molecules like trans-1,2-bis(4-pyridyl) ethene.

Novel supramolecular assembly of 3,5-dinitro-4-methylbenzoic acid and trans-1,2-bis(4-pyridyl)ethene - Varughese, S; Pedireddi, VR (Tetrahedron Letters, 2005)
A novel organic assembly, formed between 3,5-dinitro-4-methylbenzoic acid and trans-1,2-bis(4-pyridyl)ethene under hydrothermal conditions in the presence of Pr(III) and a layered structure obtained by direct co-crystallization of the reactants at ambient conditions is reported. The structures of the complexes were established, unambiguously, by single crystal X-ray diffraction methods. (c) 2005 Elsevier Ltd. All rights reserved.